2018
DOI: 10.1002/rnj.308
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Safety Through Video Monitoring

Abstract: Falls are a significant issue in rehabilitation settings and current fall prevention strategies fall short of reducing fall rates. Implementation of new video monitoring technology can help reduce fall rates in inpatient rehabilitation settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0
11

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 8 publications
1
49
0
11
Order By: Relevance
“…While video monitoring by parents of their children in the form of baby monitors have become routine in society at large,15 this has yet to become as common in the hospital environment. While concerns were raised regarding the use of such methods, similar systems have been described in other sections of the literature, and when practical issues were overcome patient care improved 16. The use of patient and public involvement is likely to be important in this particular strand, and its impact on not just patient care but also on the experience of the wider family should be acknowledged.…”
Section: Discussionmentioning
confidence: 97%
“…While video monitoring by parents of their children in the form of baby monitors have become routine in society at large,15 this has yet to become as common in the hospital environment. While concerns were raised regarding the use of such methods, similar systems have been described in other sections of the literature, and when practical issues were overcome patient care improved 16. The use of patient and public involvement is likely to be important in this particular strand, and its impact on not just patient care but also on the experience of the wider family should be acknowledged.…”
Section: Discussionmentioning
confidence: 97%
“…9 Results of another study suggest that CVM use with hospitalized adults who required supervision to prevent falls was associated with improved patient and family satisfaction. 14 In the absence of a gold standard for supervision of patients hospitalized with eating disorders, CVM technology is a tool that may balance cost, care quality, and patient experience. Given the upfront investment in CVM units, this technology may be most appropriate for institutions already using CVM for other inpatient indications.…”
Section: Discussionmentioning
confidence: 99%
“…ISSN: 2379-4550 http://digitalcommons.wayne.edu/crp, © 2017 The Author(s) 2 Licensed under Creative Commons Attribution Non-Commercial 4.0 were highly relevant. [1][2][3] We used the "Similar articles" function for each of the first three citations and reviewed abstracts for an additional 21 studies returned by PubMed.…”
mentioning
confidence: 99%
“…[1][2][3] We used the "Similar articles" function for each of the first three citations and reviewed abstracts for an additional 21 studies returned by PubMed. One additional relevant study was identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation